2015
DOI: 10.1080/01431161.2015.1065355
|View full text |Cite
|
Sign up to set email alerts
|

Estimating midday near-surface air temperature by weighted consideration of surface and atmospheric moisture conditions using COMS and SPOT satellite data

Abstract: 2015) Estimating midday near-surface air temperature by weighted consideration of surface and atmospheric moisture conditions using COMS and SPOT satellite data,The measurement of near-surface air temperature (T a ) is critically important for understanding the Earth's energy and water circulation system and for diverse modelling applications. T a data obtained from meteological ground stations are basically available but not suitable for large-scale areas, because of their spatial limitation. Remote-sensing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
1
8
1
Order By: Relevance
“…Generally, Ta values are obtained from meteorological stations 2 m above the ground, although this can be difficult in mountainous terrain. Due to the limited distribution of meteorological stations, we used an algorithm for satellite-based midday air temperature retrieval over northeast Asia [55]. This algorithm uses COMS Level 1B brightness temperature the difference between the IR 1 6 Journal of Sensors …”
Section: Estimation Of Daily Air Temperature (Ta)mentioning
confidence: 99%
“…Generally, Ta values are obtained from meteorological stations 2 m above the ground, although this can be difficult in mountainous terrain. Due to the limited distribution of meteorological stations, we used an algorithm for satellite-based midday air temperature retrieval over northeast Asia [55]. This algorithm uses COMS Level 1B brightness temperature the difference between the IR 1 6 Journal of Sensors …”
Section: Estimation Of Daily Air Temperature (Ta)mentioning
confidence: 99%
“…Generally, near-surface atmospheric temperature refers to air temperature between 1.25 and 2 m above the ground. Statistical data [ 31 ] showed that the average summer extreme maximum temperature in Nanjing is 310 K (36.85 °C).…”
Section: Thermal Radiation Modelmentioning
confidence: 99%
“…And Surface observation of satellite can be used to extracting information of near-surface environmental conditions such as Ta because satellite observation can represent better spatial coverage [14][15][16][17]. Therefore, many studies proposed Ta retrieval method with LST of satellite data to retrieve Ta in a large area [17][18][19][20]. In many studies and satellite algorithms, LST is calculated by observing the energy emitted from Earth's surface through satellite remote sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Because Ta and LST are highly correlated, it may be possible to retrieve Ta from the readings of the two IR channels (11 and 12 µm) used for LST retrieval method. In [17][18][19][20], Ta has been measured from LST by multiple regression. But there is no official LST data from Landsat-8 therefore we needed to use other data which was validated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation